The hygiene regulation of a university's canteen: The shocked of a businessman - Mohammad, Hapsah S. (2015)
The case was about a businessman who ran a canteen in a local university. In running the canteen he was helped by his family members comprising his wife, children, in-laws, siblings and his mother-in-law. He had been with the university basically since the early days of the university.He started off as an employee in the dining hall and later opened up his own canteen. One day, a committee visited the canteen and found out some hygiene regulations were violated. Three days later a 24-hour notice to evacuate was issued to him.